Afiks Pembentuk Reduplikasi Nominal Bahasa Banjar Hulu: Tinjauan Bentuk Gramatikal - Asnawi, Asnawi (GERAM: Gerakan Aktif Menulis, 2017)
This study presents the corresponding problem of affix forming the nominal reduplication of Banjar Hulu language. Language Banjar is a language used by people of Indragiri Hilir Regency Riau. Currently the state of Banjar Hulu is contaminated with modern culture and technology. Therefore, a deep review of Banjar Hulu is needed. As for the related issues related to the form of affix forming the nominal reduplication of Banjar Hulu. The purpose of this study is to describe and explain in detail about the form of affix forming of narial reduplication Banjar Hulu language. This research is manifold field research using descriptive method. Research data in the form of words spoken by informants, with data collection techniques simak libat cakap. Data validation is done by source triangulation with data analysis taking into account the form of origin and basic form. The result of this research is the finding of an affix of N-an morph which has alomorph pa-an, ba-an, ka-an, ta-an, sa-an, and sing-an.